Estimation of cytokine level IL - 4, IL - 12, IL-17 and some immune features among patients with Herpes zoster in Thi-Qar Province / Southern Iraq - Rashad, Ihsan (University of Thi-Qar Journal of Science, 2023)
Varicella-zoster virus (VZV), which was dormant in the dorsal root ganglia or cranial nerve, reactivates to produce the viral illness shingle. Immunosenescence, which includes the documented decline of cell-mediated immunity with aging, can result in in the VZV reactivation. While HZ is typically mild in young, persons who are in good health, while older individuals are more likely to experience complications. The present study was carried out during the months of July 2022 to January 2023 in the governorate of Thi-Qar We examined the levels of VZV IgG antibodies, IL-4, IL-12,IL-17 and checking level VTN in the blood of 70 HZ patients who did not suffer from superinfection. 30 individuals of a comparable age who were healthy and free of infectious and inflammatory diseases made up the control group. blood samples were collected from them and examined via the ELISA system. While the plasma vitronectin level dropped in HZ patients when in comparison to the control group, both the serum levels of the cytokines IL-4, IL-12, and IL-17 as well as the VZV IgG antibody titer considerably rose. According to the results, HZ patients without chronic illnesses had significantly greater levels of IL-17. compared to individuals suffering from chronic illnesses. Additionally, IL-12 levels were noticeably higher in females than in males. Age and sex differences were not found to be significantly different in the research.